Effect of water based therapy on water quality of hot spring in Sungai Serai, Hulu Langat - Abdul Manan, Nur Suhailah (2018)
Water is one of the most important substances on Earth which every living things need it to survive. Changes in water that specified by quantity that can be measured defines the water quality meaning. Sungai Serai Hot Spring is located in a village called Kampung Sungai Serai, Hulu Langat in Selangor which is 25km distance from Universiti Putra Malaysia (UPM) and around 30 minutes to get there. The purpose of this research was to determine the water quality before and after the water based therapy occured in Sungai Serai Hot Spring and water quality status of Sungai Serai Hot Spring by using DOE-WQI Index. The DOE-WQI index (calculated based on the Pollution Index of the Department of Environment) that was used for evaluating the water quality status of the hot spring. There were eight selected parameters which are pH, Dissolve Oxygen (DO), Turbidity, Temperature, Total Suspended Solid (TSS), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3-N) and Biochemical Oxygen Demand (BOD). The three selected sampling points were S1, clean hot spring well without therapy activities, S2, hot spring pool near S1 that occurred therapy activities and S3, the outlet of S2 pool. The samples were taken at each station once a week for six weeks started from 14th July 2017 until 14th September 2017. The water quality analysis was determined at in-situ (at the field) and ex-situ (laboratory) analyse. The average temperature of this hot spring was 42.6oC and the highest turbidity reading was at S1 throughout the weeks. Water quality status of this research was determined by using DOE-WQI Index and comparisons among sampling points by using the analysis of variance (ANOVA). The water quality index values at the study areas ranged from 56.97 to 78.75 or in Class II and Class III. Based on the Malaysia Interim National Water Quality Standards, Sungai Serai Hot Spring water is suitable for recreational use.